Blood-Brain Barrier Leakage and Microvascular Lesions in Cerebral Amyloid Angiopathy. Issue 2 (February 2019) - Freeze, Whitney M.; Bacskai, Brian J.; Frosch, Matthew P.; Jacobs, Heidi I.L.; Backes, Walter H.; Greenberg, Steven M.; van Veluw, Susanne J.
Abstract : Background and Purpose—: Cerebral amyloid angiopathy (CAA) is a common small vessel disease that independently effects cognition in older individuals. The pathophysiology of CAA and CAA-related bleeding remains poorly understood. In this postmortem study, we explored whether blood-brain barrier leakage is associated with CAA and microvascular lesions. Methods—: Eleven CAA cases (median [IQR] age=69 years [65–79 years], 8 males) and 7 cases without neurological disease or brain lesions (median [IQR] age=77 years [68–92 years], 4 males) were analyzed. Cortical sections were sampled from each lobe, and IgG and fibrin extravasation (markers of blood-brain barrier leakage) were assessed with immunohistochemistry. We hypothesized that IgG and fibrin extravasation would be increased in CAA cases compared with controls, that this would be more pronounced in parietooccipital brain regions compared with frontotemporal brain regions in parallel with the posterior predilection of CAA, and would be associated with CAA severity and number of cerebral microbleeds and cerebral microinfarcts counted on ex vivo magnetic resonance imaging of the intact brain hemisphere. Results—: Our results demonstrated increased IgG positivity in the frontotemporal ( P =0.044) and parietooccipital ( P =0.001) cortex in CAA cases compared with controls. Within CAA cases, both fibrin and IgG positivity were increased in parietooccipital brain regions compared with frontotemporal brain regions ( P =0.005 and P =0.006, respectively). The percentage of positive vessels for fibrin and IgG was associated with the percentage of amyloid-β–positive vessels (Spearman ρ=0.71, P =0.015 and Spearman ρ=0.73, P =0.011, respectively). Moreover, the percentage of fibrin and IgG-positive vessels, but not amyloid-β–positive vessels, was associated with the number of cerebral microbleeds on magnetic resonance imaging (Spearman ρ=0.77, P =0.005 and Spearman ρ=0.70, P =0.017, respectively). Finally, we observed fibrin deposition in walls of vessels involved in cerebral microbleeds. Conclusions—: Our results raise the possibility that blood-brain barrier leakage may be a contributory mechanism for CAA-related brain injury. Abstract : Supplemental Digital Content is available in the text.